FACTORS AFFECT PERFORMANCE MEASUREMENT IN CONSTRUCTION PROJECT PORTFOLIO - Adel El-Samadony; Hesham AbdelKhaleq; Diaa Khalaf (JES: Journal of Engineering Sciences, 2020)
Construction companies regularly perform multiple construction projects concurrently. Projects vary by complexity, duration, budget, variety of works, and the number of stakeholders. To determine and report the status of the ongoing portfolio of projects, methodical agreed-upon metrics should be set forth at both projects and portfolio level. The assessment of project indicators during implementation is not an easy task due to the lack of up-to-date data and factors measuring problems. The purpose of the research is to analyze common performance measurement factors, the contribution of those factors to the overall project portfolio performance, and to illustrate how to assess a projects' execution efficiency. A review for the earlier research and studies has been done to name the commonly used factors usually picked to measure the performance of portfolio and project management efficiency. A questionnaire survey conducted to project management professionals exploring their judgment in respect of relative weight contribution to each factor. AHP mathematical model used to analyses the survey responses.